Brazilian Cardiorespiratory Fitness Classification Based on Maximum Oxygen Consumption - Herdy,Artur Haddad (2016)
Abstract Background: Cardiopulmonary exercise test (CPET) is the most complete tool available to assess functional aerobic capacity (FAC). Maximum oxygen consumption (VO2 max), an important biomarker, reflects the real FAC. Objective: To develop a cardiorespiratory fitness (CRF) classification based on VO2 max in a Brazilian sample of healthy and physically active individuals of both sexes. Methods: We selected 2837 CEPT from 2837 individuals aged 15 to 74 years, distributed as follows: G1 (15 to 24); G2 (25 to 34); G3 (35 to 44); G4 (45 to 54); G5 (55 to 64) and G6 (65 to 74). Good CRF was the mean VO2 max obtained for each group, generating the following subclassification: Very Low (VL): VO2 < 50% of the mean; Low (L): 50% - 80%; Fair (F): 80% - 95%; Good (G): 95% -105%; Excellent (E) > 105%. Results: Men VL < 50% L 50-80% F 80-95% G 95-105% E > 105% G1 < 25.30 25.30-40.48 40.49-48.07 48.08-53.13 > 53.13 G2 < 23.70 23.70-37.92 37.93-45.03 45.04-49.77 > 49.77 G3 < 22.70 22.70-36.32 36.33-43.13 43.14-47.67 > 47.67 G4 < 20.25 20.25-32.40 32.41-38.47 38.48-42.52 > 42.52 G5 < 17.54 17.65-28.24 28.25-33.53 33.54-37.06 > 37.06 G6 < 15 15.00-24.00 24.01-28.50 28.51-31.50 > 31.50 Women G1 < 19.45 19.45-31.12 31.13-36.95 36.96-40.84 > 40.85 G2 < 19.05 19.05-30.48 30.49-36.19 36.20-40.00 > 40.01 G3 < 17.45 17.45-27.92 27.93-33.15 33.16-34.08 > 34.09 G4 < 15.55 15.55-24.88 24.89-29.54 29.55-32.65 > 32.66 G5 < 14.30 14.30-22.88 22.89-27.17 27.18-30.03 > 30.04 G6 < 12.55 12.55-20.08 20.09-23.84 23.85-26.35 > 26.36 Conclusions: This chart stratifies VO2 max measured on a treadmill in a robust Brazilian sample and can be used as an alternative for the real functional evaluation of physically and healthy individuals stratified by age and sex.